Aktive Arbeitsmarktpolitik in Deutschland: Bestandsaufnahme und Bewertung der mikroökonomischen Evaluationsergebnisse - Marco Caliendo; Viktor Steiner (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2005)
– Active labour market policy (ALMP) covers a multitude of state measures aimed at preventing unemployment and promoting employment. The most important ALMP programmes in quantitative terms in Germany have traditionally been further vocational training, job-creation schemes and structural adjustment measures. Recently, however, newer ALMP instruments such as settling-in allowances for firms that take on hard-to-place unemployed people and business start-up allowances for previously unemployed individuals have also gained increasing importance. A comprehensive evaluation of the effectiveness of these programmes has been made possible only relatively recently as a result of administrative data being made available for scientific evaluation research. This paper assesses the effectiveness of ALMP in Germany on the basis of a review of the available empirical evaluation studies. The account is supplemented by including the results of some international evaluation studies on AMLP instruments which are also increasingly gaining importance in Germany but for which there are currently hardly any empirical evaluation studies available here. The paper concludes with a critical appreciation of the available research findings and an outlook for future research requirements.
Keywords: 330; Arbeitsmarktpolitik - Erfolgskontrolle; Arbeitsmarktpolitik - internationaler Vergleich; Wirkungsforschung; Weiterbildungsförderung; Arbeitsbeschaffungsmaßnahme; Strukturanpassungsmaßnahme; Eingliederungszuschuss; Einstellungszuschuss; Überbrückungsgeld; Existenzgründungszuschuss; Personal-Service-Agentur; Lohnsubvention; Mini-Job; Hartz-Reform; Jugendsofortprogramm; Bildungsgutschein; Vermittlungsgutschein; Ich-AG; Arbeitslosengeld II; Einstiegsgeld; Umschulung; Arbeitsberatung; Arbeitsvermittlung; Niedrigeinkommen; berufliche Selbständigkeit; Integrierte Erwerbsbiografien